The Associations of Common Psychological Problems With Mental Disorders Among College Students - Cuijpers, Pim; Smit, Filip; Aalten, Pauline; Batelaan, Neeltje; Klein, Anke; Salemink, Elske; Spinhoven, Philip; Struijs, Sascha; Vonk, Peter; Wiers, Reinout W.; de Wit, Leonore; Gentili, Claudio; et al. (Frontiers in Psychiatry, 2021)
Psychological problems like procrastination, perfectionism, low self-esteem, test anxiety and stress are common among college students. There are evidence-based interventions available for these problems that not only have direct effects on these problems, but also indirect effects on mental disorders such as depression and anxiety disorders. Targeting these psychological problems may offer new opportunities to prevent and treat mental disorders in a way that is less stigmatizing to students. In this study we examined the association of five psychological problems with five common mental disorders (panic, generalized anxiety, bipolar, major depressive and substance use disorder) in a sample of 2,449 students from two Dutch universities. Psychological problems were measured with one item for each problem and mental disorders were measured with the Composite International Diagnostic Interview Screening Scales. Associations were examined with Poisson regression models as relative risks (RR) of the disorders as a function of the psychological problems. The population attributable fraction (PAF) indicates by what percentage the prevalence of the mental disorder would be reduced if the psychological problem was addressed successfully by an intervention. Especially generalized anxiety disorder was strongly associated with psychological problems (strong associations with stress and low self-esteem and moderately with test anxiety). The group with three or more psychological problems had a strongly increased risk for generalized anxiety (RR=11.25; 95% CI: 7.51~16.85), and a moderately increase risk for major depression (RR=3.22; 95% CI: 2.63~3.95), panic disorder (RR=3.19; 95% CI: 1.96~5.20) and bipolar disorder (RR=3.66; 95% CI: 2.40~5.58). The PAFs for having any of the psychological problems (one or more) were considerable, especially for generalized anxiety (60.8%), but also for panic disorder (35.1%), bipolar disorder (30.6%) and major depression (34.0%). We conclude that common psychological problems are associated with mental disorders and with each other. After adjustment, psychological problems are associated with different patterns of mental disorders. If the impact of the psychological problems could be taken away, the prevalence of several mental disorders would be reduced considerably. The psychological problems may provide a promising target to indirectly prevent and intervene in psychopathology in hard to reach college students with mental disorders.